THERAPEUTIC ROLE OF DIETARY FIBER AND PROBIOTICS IN LIFESTYLE DISORDERS: A NUTRITIONAL APPROACH - Ahirwar, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2025)
Lifestyle disorders such as obesity, diabetes, cardiovascular diseases, and irritable bowel syndrome (IBS) are on the rise due to poor dietary habits and sedentary lifestyles. Emerging evidence indicates that dietary fiber and probiotics play vital therapeutic roles in mitigating these conditions by modulating gut microbiota, improving metabolic parameters, and reducing systemic inflammation. This paper evaluates the combined nutritional impact of fiber and probiotics in promoting gastrointestinal and metabolic health through a hypothetical analytical model based on literature-derived data. The study compares the physiological effects of different types of dietary fiber (soluble and insoluble) and probiotic strains (Lactobacillus and Bifidobacterium species) on parameters such as serum cholesterol, fasting glucose, and gut microbial balance. The findings suggest that high-fiber diets supplemented with probiotics contribute to a significant reduction in total cholesterol (up to 12%) and fasting glucose (up to 10%), while enhancing gut microbial diversity. The synergistic action of fiber and probiotics enhances short-chain fatty acid (SCFA) production, improves bowel regularity, and strengthens intestinal barrier integrity—factors essential for preventing metabolic and gastrointestinal disorders. This paper highlights the therapeutic importance of integrating fiber-rich foods and probiotics into daily diets as a nutritional intervention to manage and prevent lifestyle diseases. From a Home Science perspective, these findings reinforce the role of functional dietary planning in promoting long-term health and wellness.